2006
DOI: 10.1111/j.1600-0420.2006.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

From basic to clinical research: a journey with the retina, the retinal pigment epithelium, the cornea, age‐related macular degeneration and hereditary degenerations, as seen in the rear view mirror

Abstract: . Purpose:  This Acta Ophthalmologica Award and Gold Medal Honorary Lecture (the Lundsgaard Gold Medal Honorary Lecture) reviews some of the work I have carried out with my mentors and many of my wonderful collaborators and research students over more than 40 years, also including related work by other groups. It concentrates on the basic electrophysiology and ultrastructure of the retina and the retinal pigment epithelium (RPE), as well as covering basic and clinical aspects of the cornea, contact lenses, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
2
0
1
Order By: Relevance
“…Further release of lytic enzymes and reactive oxygen damages the RPE cells, contributing to the formation of drusen. 61 One experiment that used cultured RPE cells fed with photoreceptor outer segments at two different oxygen concentrations found that cells kept in 40% oxygen accumulated two times more lipofuscin in 3 weeks than those kept at 8%. 62 This experiment demonstrates that oxidative reactions are implicated in lipofuscin formation.…”
Section: Pathogenic Theories For Amdmentioning
confidence: 99%
See 1 more Smart Citation
“…Further release of lytic enzymes and reactive oxygen damages the RPE cells, contributing to the formation of drusen. 61 One experiment that used cultured RPE cells fed with photoreceptor outer segments at two different oxygen concentrations found that cells kept in 40% oxygen accumulated two times more lipofuscin in 3 weeks than those kept at 8%. 62 This experiment demonstrates that oxidative reactions are implicated in lipofuscin formation.…”
Section: Pathogenic Theories For Amdmentioning
confidence: 99%
“…This membrane thickens with age. 61 The outer segment discs form as invaginations at the base of the cells and they move to the tip of the outer segment. The RPE phagocytizes the outer segment tips daily.…”
Section: Pathogenic Theories For Amdmentioning
confidence: 99%
“…Η μεμβράνη του Bruch έχει διττό ρόλο, αφενός λειτουργεί σαν ηθμός κατά την ανταλλαγή αερίων, θρεπτικών συστατικών και μεταβολικών αποβλήτων αφετέρου παίζει στηρικτικό ρόλο για τις ανώτερες στιβάδες κυττάρων. Οποιαδήποτε διαταραχή του μελάγχρου επιθηλίου και της μεμβράνης του Bruch, όπως για παράδειγμα η πάχυνση της τελευταίας με το γήρας, μπορεί να οδηγήσει σε συσσώρευση μεταβολικών αποβλήτων και κυτταρικών υπολειμμάτων, ανάμεσα στον RPE και στην μεμβράνη του Bruch συνεισφέροντας στον σχηματισμό των drusen [76]. Σε μοριακό επίπεδο, οι βιολογικές διεργασίες που πυροδοτούν την διαταραχή της λειτουργίας των ανωτέρω δομών του αμφιβληστροειδούς, οδηγώντας στην εμφάνιση της AMD, μόλις έχουν αρχίσει να ταυτοποιούνται.…”
Section: αιτιοπαθογένειαunclassified